The Multiple-Pathways of Personality Traits on Fitness Behavior: The Mediating Role of Ethical Orientation - Meng Meng; Rong-Hai Su; Kohei Kogiso; Deng Wang; Lin Chen; Wei Wei; Chen Chen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This paper constructs a multi-impact path model of personality traits on fitness behavior, based on theories of personality psychology and normative ethics, empirically tests the relationships between constructs in the model, and reveals the influence mechanisms of economic value orientation and machiavellian personality traits on fitness behavior. A total of 278 fitness enthusiasts from 26 provinces in China, each with at least one year of fitness experience, were selected as research subjects using convenience and snowball sampling methods. A questionnaire survey was conducted to examine the relationships among their personality traits, moral orientation, and fitness behavior. Descriptive and visual analysis was performed using SPSS 25.0 and R 4.2.2, and the structural equation model of the multi-impact path model on fitness behavior was tested using AMOS 20.0. (1) Economic value orientation personality traits significantly positively influence normative fitness behavior; (2) Machiavellian personality traits significantly positively influence anomie fitness behavior; (3) Teleological ethics partial mediating role between economic value orientation personality traits and normative fitness behavior; (4) Deontological ethics partial mediating role between machiavellian personality traits and anomie fitness behavior. itness enthusiasts with economic value orientation personality traits who adhere to fitness pragmatism are more likely to exhibit a sense of social responsibility, pay more attention to pursuing moral purposes, focus on social fairness and justice, and the results and impacts of fitness behavior, thereby leading to more normative fitness behavior. Conversely, those with machiavellian personality traits who adhere to utilitarianism often face dilemmas where their moral beliefs conflict with practical benefits and disadvantages. They are more likely to violate moral standards and social order, resulting in unethical anomie fitness behavior.